WORD FORMATION AS A LANGUAGE SYSTEM AND ITS ROLE IN THE VOCABULARY ENRICHMENT ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Language is a dynamic system, and one of its fascinating aspects is the process of word formation. It plays a crucial role in enriching our vocabulary and expanding our linguistic abilities. Word formation refers to the creation of new words or the modification of existing ones to convey different meanings or nuances. Through various word formation processes such as derivation, compounding, blending, and conversion, languages evolve and adapt to meet the diverse needs of communication.This process is essential for the evolution and expansion of a language, as it allows speakers to express new ideas, concepts, and experiences.